A Minority Subpopulation of CD133+/EGFRvIII+/EGFR− Cells Acquires Stemness and Contributes to Gefitinib Resistance. (10th April 2013) - Liu, Xu‐Jie; Wu, Wen‐Tao; Wu, Wei‐Hua; Yin, Feng; Ma, Si‐Hai; Qin, Jia‐Zhen; Liu, Xiu‐Xiu; Liu, Yi‐Nan; Zhang, Xiao‐Yan; Li, Peng; Han, Shuo; Liu, Kai‐Yu; et al.
Summary Aims To study the contribution of epidermal growth factor receptor variant III (EGFRvIII) to glioblastoma multiforme (GBM) stemness and gefitinib resistance. Methods CD133+ and CD133− cells were separated from EGFRvIII+ clinical specimens of three patients with newly diagnosed GBM. Then, RT‐PCR was performed to evaluate EGFRvIII and EGFR expression in CD133+ and CD133− cells. The tumorigenicity and stemness of CD133+ cells was verified by intracranial implantation of 5 × 103 cells into immunodeficient NOD/SCID mice. Finally, cells were evaluated for their sensitivity to EGFR tyrosine kinase inhibition by gefitinib. Results RT‐PCR results showed that the sorted CD133+ cells expressed EGFRvIII exclusively, while the CD133− cells expressed both EGFRvIII and EGFR. At 6–8 weeks postimplantation, CD133+/EGFRvIII+/EGFR− cells formed intracranial tumors. Cell counting kit‐8 results showed that the IC50 values of the three isolated EGFRvIII+ cell lines treated with gefitinib were 14.44, 16.00, and 14.66 μM, respectively, whereas the IC50 value of an isolated EGFRvIII− cell line was 8.57 μM. Conclusions EGFRvIII contributes to the stemness of cancer stem cells through coexpression with CD133 in GBMs. Furthermore, CD133+/EGFRvIII+/EGFR− cells have the ability to initiate tumor formation and may contribute to gefitinib resistance.